An Elite Controller of Picornavirus Infection Targets an Epitope That Is Resistant to Immune Escape - Bell, Michael P. (Public Library of Science, 2014)
The emergence of novel viral pathogens can lead to devastating consequences in the infected population. However, on occasion, rare hyper-responsive elite controllers are able to mount a protective primary response to infection and clear the new pathogen. Factors distinguishing elite controllers from other members of the population are not completely understood. We have been using Theiler's murine encephalomyelitis as a model of primary infection in mice and clearance of the virus is limited to one MHC genotype capable of generating a protective response to a single viral peptide VP2(121-130). The genetics of host susceptibility to TMEV, a natural mouse pathogen, has been studied extensively and non-protective CD8 responses to other peptides have been documented, however, little is known why the protective response to infection focuses on the VP2(121-130) peptide. To study this question, we have generated TMEV mutants that encode for mutations within the VP2(121-130) peptide. We find that very few of mutants are able to assemble and infect in vitro. These mutations are not related to virus RNA structure since non-coding mutations do not interfere with assembly. In the rare event when functional VP2(121-130) mutant viruses did emerge, they were attenuated to some level or retained the ability to develop an immune response to the wild-type VP2(121-130) sequence, demonstrating that the virus is incapable of escaping the protective response. These findings advance our understanding of how characteristics of the host immune response and an infectious agent can interact to lead to the appearance of rare super controllers in a population. Furthermore, the immutable nature of the viral antigen highlights the importance of choosing appropriate vaccine antigens and has implications for the development of agents that are able to generate protective CD8 T-cell responses.